High-Performance Thick-Film All-Polymer Solar Cells Created Via Ternary Blending of a Novel Wide-Bandgap Electron-Donating Copolymer - Fan, Baobing; Zhu, Peng; Xin, Jingming; Li, Ning; Ying, Lei; Zhong, Wenkai; Li, Zhenye; Ma, Wei; Huang, Fei; Cao, Yong (Advanced Energy Materials, 2018)
A novel wide-bandgap electron-donating copolymer containing an electrondeficient, difluorobenzotriazole building block with a siloxane-terminated side chain is developed. The resulting polymer, poly(4,8-bis(4,5-dihexylthiophen2- yl) benzo[1,2-b: 4,5-b'] dithiophene-co-4,7-di(thiophen-2-yl)-5,6-difluoro-2-(6( 1,1,1,3,5,5,5-heptamethyltri-siloxan-3-yl) hexyl)-2H-benzo[d][1,2,3] triazole (PBTA-Si), is used to successfully fabricate high-performance, ternary, all-polymer solar cells (all-PSCs) insensitive to the active layer thickness. An impressively high fill factor of approximate to 76% is achieved with various ternary-blending ratios. The optimized all-PSCs attain a power conversion efficiency (PCE) of 9.17% with an active layer thickness of 350 nm and maintain a PCE over 8% for thicknesses over 400 nm, which is the highest reported efficiency for thick all-PSCs. These results can be attributed to efficient charge transfer, additional energy transfer, high and balanced charge transport, and weak recombination behavior in the photo-active layer. Moreover, the photoactive layers of the ternary all-PSCs are processed in a nonhalogenated solvent, 2-methyltetrahydrofuran, which greatly improves their compatibility with large-scale manufacturing.
Keywords: all-polymer solar cells; high performance; siloxane-functionalized side chains; ternary blends; thick active layers